Application level interoperability on IaaS cloud migration - Zahara, Soffa; Sumpeno, Surya; Pratomo, Istas (Association for Scientific Computing Electrical and Engineering, 2017)
The increasing awareness of people about several benefits using cloud computing technology caused a lot of organizations, companies, and agencies are switching from utilizing physical infrastructure to cloud infrastructure, especially IaaS. Considering the strong market enthusiastic about cloud computing, cloud companies were racing competitions offer the best products with various advantages. In the process of utilizing cloud computing technology there are circumstances in which the company wants to move its infrastructure to other cloud providers caused by various aspects in order to meet better expectations of to the new provider. However, there are many obstacles in practice in the process of transfer system between two different environment or can be called migration. One of them is a vendor lock-in that caused system cannot be function properly especially application functionality after migration. This paper introduces improvement method of testing interoperability between systems that were migrated between different cloud providers which use different hypervisor technology. We also conduct interoperability application testing between several cloud providers.